Ajustamento de redes gps em conformidade com as exigências da lei 10.267/2001 - da Silva, Heloísa Alves [UNESP]; Monico, João Francisco Galera [UNESP] (My University, 2009)
In the Brazil, several have been the applications of GPS and with the introduction of the Law 10.267/2001 that among other dispositions, it treats of the georeferencing of the rural parcels. However, most of the commercial softwares of processing and adjustment of GPS data doesn't allow that the users may evaluate their results in a reliable way. For example, the constraints are normally used as absolute, which provides results with very optimists precisions. The adoption of additional analyses and the implementation of softwares can reduce these kinds of problems. Thus, it was developed a software for adjustment of GPS networks, aiming to assist in a reliable way the requirements of the Law 10.267/2001. In this context, in this work it is analyzed the adjustments of GPS networks, utilizing absolute and relative constraints. In the case of the last one, the adjustments were accomplished considering and not considering the correlations among the coordinate positions.
Adjustment of gps networks in accordance with the requirements of law 10267/2001
Keywords: GPS Network; Positioning; Stochastic Model; coordinate; data processing; GPS; positioning; software; stochasticity; Brazil; South America